Image segmentation using transfer learning and Fast R-CNN for diabetic foot wound treatments - Huang, Huang-Nan; Zhang, Tianyi; Yang, Chao-Tung; Sheen, Yi-Jing; Chen, Hsian-Min; Chen, Chur-Jen; Tseng, Meng-Wen (Frontiers in Public Health, 2022)
Diabetic foot ulcers (DFUs) are considered the most challenging forms of chronic ulcerations to handle their multifactorial nature. It is necessary to establish a comprehensive treatment plan, accurate, systematic evaluation of a patient with a DFU. This paper proposed an image recognition of diabetic foot wounds to support the treatment plan’s effective execution. In the severity of a diabetic foot ulcer, we refer to the current qualitative evaluation method commonly used in clinical practice, developed by the International Working Group on the Diabetic Foot: PEDIS index, and the evaluation made by physicians. The deep neural network, convolutional neural network, object recognition, and other technologies are applied to analyze the classification, location, and size of wounds by image analysis technology. The image features are labeled with the help of the physician. The Object Detection Fast R-CNN method is applied to these wound images to build and train machine learning modules and evaluate their effectiveness. In the assessment accuracy, it can be indicated that the wound image detection data can be as high as 90%.